Identification and Prioritization of Effective Factors on Increasing the Short-Term E-Learning Systems’ Effectiveness in University Jihad in Khorasan Razavi - Abdolali Keshtegar (Journal of Global Pharma Technology, 2017)
In the present era, computer and subsequently internet are ones of the main human inventions which led to some great changes in human life that has caused a virtual world and an incentive for universities in order to invest in e-Learning section. But what that makes the importance of discussion clear is making attempt to succeed in using e-learning system and checking these systems’ success rate and unsuccessful attempt for implementing e-learning will cause loss of capital. This research was conducted with the purpose of identifying and ranking the effective elements on increasing the effectiveness of short-term e-learning systems in university Jihad in Khorasan Razavi. Therefore, the components and indicators of e-learning systems’ effectiveness assessment were suggested according to previous studies, then, a questionnaire was provided to the e-Learning learners of the of University Jihad Education Deputy of Mashhad with the aim of identifying the components of measuring the effective factors of e-Learning systems in order to assess the validity and appropriateness of the proposed components and indicators. Collected data of questionnaire was processed by software SPSS and one-sample t-test and Pearson correlation coefficient test have been used to analyze data. Six components were finalized with 26 indicators. The main components respectively include: 1- school characteristic. 2- Information quality.3- Quality of system and infrastructure. 4- Service quality. 5- Support factors. 6- Comprehensive characteristics.Keywords: E-Learning system, E-Learning’s assessment components.